Age and growth estimates for the starry smoothhound (mustelus asterias) in the northeast atlantic ocean - Farrell, E. D.; Mariani, S.; Clarke, M. W. (Oxford University Press (OUP), 2010)
Age, growth, and longevity were estimated for the starry smoothhound (Mustelus asterias), based on the interpretation of sectioned vertebrae of 106 males (35 - 104 cm stretch total length, STL) and 114 females (44 - 112 cm STL). Growth curves were fitted to length-at-age data using von Bertalanffy and Gompertz models. The three-parameter von Bertalanffy growth function (VBGF) provided the best statistical fit to the male data (L(infinity) = 103.7 cm STL, L(0) = 38.1 cm STL, k = 0.195 year(-1)). The Gompertz growth function provided the best statistical fit to the female data, although the estimated parameters were biologically unreasonable. Therefore, the three-parameter VBGF was also accepted for females (L(infinity) = 123.5 cm STL, L(0) = 34.9 cm STL, k = 0.146 year(-1)). Longevity was estimated to be 13 and 18.3 years for males and females, respectively. The length weight relationship is also presented for 304 male and 424 female M. asterias. The von Bertalanffy model was fitted to the weight-at-age data. These estimates can form the basis of future work on the assessment and management of this species.